Prevalensi Infeksi Cacing Usus Golongan Soiltransmittedhelmints (STH) Pada Siswa Sekolah Dasar Di Kelurahan Abiantubuh Baru Mataram - Irna Il Sanuriza; Dwi Kartika Risfianty; Pahmi Husain; Khaerul Ihwan; Baiq Naili Dewi Atika; Siti Jannatul Mardiani; Husnul Khotimah (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2021)
Disability is one of the most attention-catching infections (neglected diseases) which didn’t cause a lot of casualties and not a sudden outbreak but it can result in a slow death by slowly roasting the body’s healthy organs until it causes permanent and lowers child intelligence. This research was to compare the prevalence of worm infection of class Soil-Transmitted Helminths on elementary school students or madrasah ibtidaiyah students in the village Abian Tubuh Baru sub-district Sandubaya in 2008 and checking out the number of cases of worm infections according to this type of worm. The methods of research used in this study is observational descriptive methods and microscopic methods to use a microscope to identify a type of worm from stool sample drawn from students on elementary school/madrasah ibtidaiyah in Abian Tubuh Baru village. The result of that feces examination indicates that there are three kinds of worms are ringworm (Ascaris lumbricoides), whipworm (Tricuris trichiura), and hookworm (Ancylostoma duodenale dan Necator americanus). The most numerous types of worms found are these Ascaris lumbricoides as big as 75,67%.